Association of Aggressive Driving Behavior with Sociodemographic and Work-Related Factors in Jeepney Drivers in Rondon Project 6 Terminal with Route Project 6-TM-Kalaw/Pier - 4 0 16; 5
Aggressive driving behavior is one of the major causes of vehicular accidents today. Its dangers are apparent; hence, understanding its consequences may help in preventive measures to ensure road safety. In the Philippines, jeepney serves as the number onepublic transport system which carries millions of passengers per day. In this study, the association of socio-demographic and work-related factors with the aggressive driving behavior of jeepney drivers in Rondon Project 6 terminal station with Project 6-TM Kalaw/Pier route was determined using simple logistic regression analysis. Results showed; that among the socio-demographic factors, the respondent's age (> 40 years old) (OR = 0.329; p=0.022) was significantly associated with aggressive driving. The prevalence of aggressive driving behavior among the jeepney drivers was 12.43%. This study recommends that in-depth knowledge of the aggressive driving behavior of jeepney drivers be taken in order to improve road safety in Metro Manila.
Keywords: 2 -- 0; 6; 20; 20; 2